Optimalisasi Peran Badan Amil Zakat Nasional (Baznas) Kabupaten Bondowoso Dalam Mewujudkan Masyarakat Cerdas, Sehat Dan Berdaya. - Mas'ud Mas'ud; Munawir Munawir (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
Those who give and manage zakat, infaq, and shodaqoh (alms) contribute and play a part in solving various current community issues, one of which is helping underprivileged communities create a smart, healthy, and competitive society. Therefore, to strengthen and structure the zakat system and other forms of zakat, its implementation must be managed by an institution known as the National Zakat Agency (BAZNAS). The goal is to ensure a professional, optimal, and effective zakat system and management. The formulation of the problem in this study includes the following: first, how to optimize the role of BAZNAS Bondowoso Regency in realizing a smart society. Second, How to optimize the role of BAZNAS Bondowoso Regency in realizing a healthy society. Third, how to optimize the role of BAZNAS Bondowoso Regency in realizing a competitive society. Optimization of the National Zakat Agency (BAZNAS) based on the theory of the basic concept of zakat institutions and their existing strategies.